2006
DOI: 10.1097/00004650-200601000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Patientsʼ Perceptions of Spirituality and the Nurse as a Spiritual Care Provider

Abstract: This qualitative study explored patients' perceptions of spirituality and of the nurse as a spiritual care provider. Semistructured interviews were conducted with 8 adults older than 21, who were living at home, and had been discharged from the hospital within the past 3 months having had at least a 5-day length of stay. Participants agreed that during their hospitalization, nurses were kind and caring but these behaviors were not perceived as spiritual care. Study findings suggest that patients do not perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…Cavendish et al 5 found in a patient study that patients perceived that nurses did not have enough time to provide spiritual care. This is in line with Edwards et al 8 who in their meta-study of qualitative research found that according to nurses and patients having time to listen is a facilitator for spiritual care.…”
Section: Provision Of Information On Services %mentioning
confidence: 99%
See 1 more Smart Citation
“…Cavendish et al 5 found in a patient study that patients perceived that nurses did not have enough time to provide spiritual care. This is in line with Edwards et al 8 who in their meta-study of qualitative research found that according to nurses and patients having time to listen is a facilitator for spiritual care.…”
Section: Provision Of Information On Services %mentioning
confidence: 99%
“…2,3 Although spiritual care is commonly regarded as a nursing task, in practice it is often provided inadequately. [4][5][6] Grant et al 7 conclude that patients find it important that their professional caregivers provide spiritual support noting that: All accepted that if spiritual issues or questions were raised these should be responded to, but most had neither the time nor the skill to 'do spiritual care(p. 374). 7 In response to these concerns training has been reported as one way of increasing not just skills but also facilitating the required attitude and facility for spiritual care giving.…”
Section: Introductionmentioning
confidence: 99%
“…For some clients, this may not be problematic if spiritual needs are not present or if clients are uninterested in discussing their spiritual needs with health care professionals. For other clients, the failure to assess and address spiritual needs impedes wellness (Cavendish et al, 2006;Davidson, Boyer, Casey, Matzel, & Walden, 2008). Even clients who initially indicate they are uninterested in discussing their spiritual needs appear to appreciate practitioners conducting an initial spiritual assessment to determine their desires (Williams et al).…”
Section: Implications For Practicementioning
confidence: 99%
“…Developing familiarity with common spiritual needs across a number of traditions can help practitioners identify spiritual needs by sensitizing them to their possible presence (Cavendish et al, 2006;Davidson et al, 2008;Hodge & Horvath, 2011). It is easier to assess and address spiritual needs if one has some sense of how spiritual needs are manifested in health care settings.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation